DECISION USEFULNESS OF FINANCIAL INFORMATION: THE ROLE OF AUDIT AND IFRS - Embong, Zaini; Rad, Sayed Sajad Ebrahimi (Jurnal Akuntansi dan Keuangan Indonesia, 2018)
We examine the usefulness of financial information given different circumstances, pre and post- International Financial Reporting Standards (IFRS) adoption and audit quality. The usefulness of information is deduced from the association between information quality and investment efficiency. IFRS is said to promote more informative financial information and hence should increase the decision usefulness of the reported information. In practice, auditors are the center of reference in the preparation of financial report and empirical evidence shows that quality audit enhances the credibility of reported information. This study aims to examine and compare the roles of IFRS and audit quality in the association between financial information quality and investment efficiency. The results from a sample of 558 firms provide support that financial information quality is significantly related to investment efficiency indicating decision usefulness of reported information. However, despite the contention that IFRS leads to a more informative financial report, the results show that IFRS does not strengthen the relationship between information quality and investment efficiency. The result for audit quality, on the other hand, is significant indicating that reported information is more useful to decision-makers when it is audited by the quality audit firm.